STATISTICAL ANALYSIS OF PATHOLOGICAL ANATOMY OF THROMBOEMBOLIC COMPLICATIONS IN CORONAVIRUS INFECTION - Shokhrukh R. Omonov; Khasan Z. Tursunov; Khamza N. Babaev; Nigora Kh. Kholieva (Central Asian Journal of Medicine, 2023)
This article compares the scientific findings of world scientists aimed at elucidating the pathological anatomy of thromboembolic complications in the composition of coronavirus infection and statistical analysis of coronavirus infection in our country. Statistical analysis showed that complications of thromboembolism in the period from 2019 to 2021 as part of coronavirus infection in the world will be 37%, of which 14% will be pulmonary embolism. Thromboembolic complications in patients with coronavirus infection, including sinus thrombosis, are currently considered the most common cause of death from Covid infection.